REMUNERASI DAN PROBLEM REFORMASI BIROKRASI DI INDONESIA - SUSANTO, HAPPY (PUBLISIA (Jurnal Ilmu Administrasi Publik), 2016)
Remuneration emerged as a solution to the issues of corruption that afflicts a number of civil servants (PNS) and officials in the bureaucracy. Remuneration is expected to improve their performance to be better, but in fact the opposite happened. In a number of media reports, many people who work in the government who arenât absent from corrupt practices, although they have a high salary. Remuneration, which is in the study of literature is also referred to as pay-for-performance system, the use of performance measurement associated with reward (compensation) as appropriate. With the proper compensation, employees no longer think about looking for financial benefits in ways that are not justified by law. On the other hand, the low level of compensation will affect the performance of employees is also low. The implementation of remuneration is one of the governments efforts to lead to good governance, coupled with bureaucratic reform. There is a strong link between the compensation and quality of public services. Improving the quality of public services is also determined by their motivation, but the growth of a great motivation is because of their high compensation. In its development, the remuneration is not absent from criticism. In fact, arguably the remuneration policy and objectives are often misguided. Therefore, governments need to include these policies with strict sanctions if there are employees or officials who make mistakes, disciplinary, and violated the rules.